Three historical-critical theses concerning school curricula - Pasqualini, Juliana Campregher [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this theoretical essay is to analyse school curricula from a historical-critical approach. We present the results of the first stage of our postdoctoral research, which, as a whole, addressed the problem of the nature and specificity of early childhood education curricula. The findings presented in this paper result from the effort of a theoretical and conceptual delimitation of the general conception of curricula in historical-critical pedagogy. These results are presented in the form of theses, which were identified, systematised and formulated based on conceptual and bibliographical investigations of selected works from the historical-critical theoretical field concerning the problem at hand. Three theses concerning the general conception of curricula are presented and supported, which highlight: 1) their political dimension and mediating nature, from the dialectic between objectives and means of education; 2) the defense of the classics, showing the clarification needed of this historical-critical principle in order to avoid a simplifying and abstract treatment; 3) the relationship between curriculum content and the problems posed by global social practice, based on the methodological concept of problematisation.
Keywords: Curriculum; Historical-critical pedagogy; School education